Dakwah-Based Educational Strategies for Enhancing Community Understanding of Agricultural Zakat in Belawa District, Wajo Regency - Santalia, Indo; Khatimah, Husnul; Umrati, Umrati (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This study explores the role of dakwah-based educational strategies in improving community understanding of agricultural zakat in Belawa District, Wajo Regency. The research aims to identify the existing dakwah-based educational strategies, assess the community’s knowledge of agricultural zakat, and examine the challenges faced in enhancing this understanding. Using a qualitative descriptive method, the study incorporates theological-normative, sociological, and psychological approaches. Data were gathered from primary sources, including religious leaders, government officials, and community leaders, as well as secondary sources through relevant documentation. Instruments such as observation guidelines, interview protocols, and documentation were employed for data collection. The analysis involved data reduction, presentation, verification, and conclusion drawing. The findings indicate that the community's understanding of agricultural zakat remains limited, with many believing that donating an unspecified amount of money after harvest at the mosque constitutes agricultural zakat. The study highlights the importance of dakwah-based educational strategies in improving this understanding, as current socialization efforts by relevant authorities have been inadequate. These findings emphasize the need for a more effective approach in educating the community about agricultural zakat to strengthen religious and social awareness.